A theory of delegated contracting - Wolfgang Gick (Research Institute of Industrial Economics (IFN), 2016)
Delegated contracting describes a widely observable agency mode where a top principal, who has no direct access to a productive downstream agent, hires an intermediary to forward a sub-contract with specified output targets and payments. The principal makes the payment to the intermediary contingent on production taking place; the intermediary is protected by limited liability and paid a bonus. I characterize the optimal grand-contract with a continuum of agent types by using optimal control techniques with a scrap value function. Delegation proofness is reached through paying the intermediary what she could obtain by deviating. This rent is shown to be convex and increasing in the contracting space. There is internal verification of the ex-post state to reach compliance. The principal uses cutoff structures instead of additional output distortions. A leftbound incentive alignment principle between principal and intermediary applies. The paper so delivers a general analysis of the loss of control in vertical hierarchies.
Keywords: D23; D73; L51; 330; Delegated contracting; Vertical hierarchies; Internal verification; Adverse selection; Limited liability; Cutoff structures; Leftbound incentive alignment